KUALITAS PELAYANAN DOKUMEN DAN KECEPATAN BONGKAR MUAT GENERAL CARGO - Umagapi, Brata Wuntara; Amonalisa, Siska; Lesmini, Lies (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2016)
The studyâs objective is to analyze the relationship of the documents service quality (X1) and the speed of loading and unloading of general cargo (X2) with service user satisfaction (Y) in Tubagus Jaya PT Maritim, either individually or jointly. Research using quantitative methods, with a population of consumers Tubagus Jaya PT Maritim many as 67 people and the determination of a sample of 30 people. Data were analyzed by using multiple regression and multiple linear regression, simple correlation and partial correlation. Results: 1. There is a correlation between the quality of service of documents by the service user satisfaction is r of 0.794 means there is a very strong relationship and the direction (positive), and the regression hypothesis there is no significant relationship to thitung greater than t table (10.529> 1.669) or hypothesis H1 be accepted. 2.Hasil correlation between the speed of loading and unloading of general cargo with service user satisfaction obtained r of 0.651 means a strong relationship and the direction (positive), and the hypothesis of regression showed a significant relationship that is greater than ttable thitung (6.914> 1.669) or hypothesis H2 be accepted. 3. Results of correlation between the quality of service of documents and speed of loading and unloading of general cargo together with service user satisfaction obtained r of 0.814 means the relationship is very strong and direct (positive), and F count larger than F table (62.871> 3.140) or the research hypothesis H3 is received.